"KiDS and Diabetes in Schools" project: Experience with an international educational intervention among parents and school professionals. Issue 4 (4th March 2018) - Bechara, Glaucia Margonari; Castelo Branco, Fernanda; Rodrigues, Avelino Luiz; Chinnici, Daniela; Chaney, David; Calliari, Luis Eduardo P.; Franco, Denise Reis
Abstract : Background: Although it is known that school care is a major challenge in diabetes treatment, there is still no published international initiative. Objectives: The aims of this study were to introduce an international educational intervention tool, the International Diabetes Federation (IDF) KiDS and Diabetes in Schools project (KiDS project), and to describe its impact on diabetes knowledge and behavior of caregivers and school professionals. Methods: The KiDS project was developed with the support of IDF and the International Society for Pediatric and Adolescent Diabetes and provides online free material in 10 languages, directed to caregivers and school personnel. A pilot evaluation of the KiDS intervention was performed in Brazil. An educational intervention was conducted in 5 primary schools, with 42 parents and school staff, followed by 2 individual interviews after 1 and 3 months. The results were evaluated in a qualitative study with a descriptive design based on content analysis. Results: School staff acquired new knowledge on diabetes and its treatment. They felt more confident when helping students with diabetes and said the educational intervention promoted a positive impact on the teacher‐student relationship, on the caring for health, and on school infrastructure. Family members of children with diabetes stated that the educational intervention gave them an opportunity to strengthen and update information on treatment and improve their knowledge. Conclusions: The KiDS project is the first international tool directed to foster a safe and supportive environment and a better understanding of diabetes in schools. In this pilot evaluation, it achieved the goal of informing and changing the behavior of parents and school staff, thus improving the care provided to children with diabetes in schools.